New method of evaluating spatial quality for innovation districts: A case study of Haidian and Chaoyang districts, Beijing - Yixing Duan; Da Lu; Lanchun Bian (Frontiers of Architectural Research)
Science and technology innovation has become the core driving force of urban development, and innovation spaces as the carriers of innovation activities have evolved continuously, forming the emerging model of innovation districts in recent years. However, the evaluation standard of innovation spaces has not changed with the evolution of the model, and the evaluation method that focuses on economic benefits still dominates the mainstream. As a result, the construction of innovation spaces around these indicators and guidelines lags behind the advanced level.In this paper, we have systematically sorted out the relevant research progress of innovation districts, established a set of cases with global typicality, combined the dual attributes of “innovation characteristics + urban characteristics,” constructed a research framework for the spatial quality of innovation districts based on the dual perspectives of “innovation space,” and summarized the spatial quality evaluation model through analysis. We do an empirical study on Haidian District to find out how well innovation districts work in terms of space, find typical clusters, and come up with the most important aspects of their space quality. In order to observe the applicability of this method, it is also applied to the urban health check-up in Chaoyang District, Beijing. Through the expert seminar, the evaluation and analysis method of spatial quality of innovative urban areas is further verified and discussed. The results show that the integration of innovative urban areas and urban structures, and the collaborative development of innovative industries and high-quality spaces are the keys to promote the common development of innovative economy and cities. The new evaluation method can effectively measure the quality of innovation spaces, and has certain transferability.